2017
DOI: 10.1177/0030222817729616
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Toward Euthanasia Among Turkish University Students

Abstract: This study aims to examine perceptions and attitudes toward euthanasia among university students who are pursuing bachelor's degrees. Although the legalization and application of euthanasia are discussed commonly by health-care professionals and partially by lawyers, the ideas of other segments of society, especially university students, are taken place very rarely. The research was conducted descriptively to determine the ideas of 1,170 students at Kastamonu University from six different departments: arts and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 14 publications
1
7
2
1
Order By: Relevance
“…As for sociodemographic characteristics, none seemed to distinguish each group of attitude toward MAiD, except for gender. In contrast to some study findings (Castelli Dransart et al, 2019;Emanuel et al, 2016;Ulas Karaahmetoglu & Kutahyalioglu, 2019), female participants seem to favor MAiD more in this study. As argued by Mercadillo et al (2011), compassion, empathetic sensitivity, and manifestation of extra care for others through emotional appraisal, may have influenced female support for MAiD as a way to end suffering.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…As for sociodemographic characteristics, none seemed to distinguish each group of attitude toward MAiD, except for gender. In contrast to some study findings (Castelli Dransart et al, 2019;Emanuel et al, 2016;Ulas Karaahmetoglu & Kutahyalioglu, 2019), female participants seem to favor MAiD more in this study. As argued by Mercadillo et al (2011), compassion, empathetic sensitivity, and manifestation of extra care for others through emotional appraisal, may have influenced female support for MAiD as a way to end suffering.…”
Section: Discussioncontrasting
confidence: 99%
“…As for sociodemographic characteristics, none seemed to distinguish each group of attitude toward MAiD, except for gender. In contrast to some study findings (Castelli Dransart et al., 2019; Emanuel et al., 2016; Ulas Karaahmetoglu & Kutahyalioglu, 2019), female participants seem to favor MAiD more in this study. As argued by Mercadillo et al.…”
Section: Discussioncontrasting
confidence: 99%
“…There are studies showing how much the subject of euthanasia is included in nursing curricula that have not been found in Turkey. Studies on euthanasia are generally related to the knowledge, perception, perspective, and attitudes of physicians, nurses or students toward euthanasia and the factors affecting them ( 10 13 ). Therefore, training should be organized to enable different disciplines such as physicians, nurses and midwifery students to create their arguments.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, there are some studies in which the views of healthcare professionals and students are discussed. Studies on euthanasia in Turkey are generally about the knowledge, perception, view, and attitudes of physicians, nurses or students toward euthanasia and the factors affecting them ( 10 13 ). No studies have been found showing how much euthanasia is included in the curriculum.…”
Section: Introductionmentioning
confidence: 99%
“…Iz toga zaključujemo da studenti nisu a priori isključivi u pogledu neodobravanja eutanazije, već smatraju da postoje određene okolnosti u kojima je ona opravdana (na primjer s česticom č14, »Pasivna eutanazija je opravdana ako pacijent boluje od neizlječive bolesti.«, slaže se ili u potpunosti slaže više od trećine studenata). Konačno, imajući na umu strukturu uzorka ovog rada, zaključujemo da ovi nalazi uvelike potvrđuju nalaze ranijih istraživanja (Karaahmetoglu i Kutahyalioglu, 2017;Leppert i dr., 2013;Poli, 2018;Sikora, 2009;Sharp, 2017;Stolz i dr., 2015;Tomašević i Jurun, 2007;Weiss i Lupkin, 2010) u kojima se pokazalo da su eutanaziji skloniji ispitanici niže dobne skupine, oni koji žive u urbanim sredinama te oni višeg stupnja obrazovanja.…”
Section: šTo Studenti Odabranih Sastavnica Suz-a Misle O Pasivnoj Eutunclassified